Correlation of Kondo effect and molecular conformation of the acceptor molecule in the TTF-TCNE charge transfer complex. (22nd October 2018) - Stoll, Paul; Lotze, Christian; Ladenthin, Janina N; Umbach, Tobias R; Fernández-Torrente, Isabel; Franke, Katharina J
Abstract: A Kondo resonance has been observed on purely organic molecules in several combinations of charge transfer complexes on a metal surface. It has been regarded as a fingerprint of the transfer of one electron from the donor to the extended π orbital of the acceptor's LUMO. Here, we investigate the stoichiometric checkerboard structure of tetrathiafulvalene (TTF) and tetracyanoethylene (TCNE) on a Au(1 1 1) surface using scanning tunneling and atomic force microscopy at 4.8 K. We find a bistable state of the TCNE molecules with distinct structural and electronic properties. The two states represent different conformations of the TCNE within the structure. One of them exhibits a Kondo resonance, whereas the other one does not, despite of both TCNE types being singly charged.